Tumor treating induced fields: a new treatment option for patients with glioblastoma - Cai, Zehao; Yang, Zukai; Wang, Ying; Li, Ye; Zhao, Hong; Zhao, Hanwen; Yang, Xue; Wang, Can; Meng, Tengteng; Tong, Xiao; Zheng, Hao; He, Zhaoyong; et al. (Frontiers in Neurology, 2024)
Purpose Currently, a range of electromagnetic therapies, including magnetic field therapy, micro-currents therapy, and tumor treating fields, are under investigation for their potential in central nervous system tumor research. Each of these electromagnetic therapies possesses distinct effects and limitations. Our focus is on overcoming these limitations by developing a novel electric field generator. This generator operates by producing alternating induced currents within the tumor area through electromagnetic induction. Methods Finite element analysis was employed to calculate the distribution of electric fields. Cell viability was assessed using the CCK-8 assay. Tumor volumes and weights served as indicators to evaluate the effectiveness of TTIF. The in-vivo imaging system was utilized to confirm tumor growth in the brains of mice. Results TTIF significantly inhibited the proliferation of U87 cells both in vitro and in vivo. Conclusion TTIF significantly inhibited the proliferation of U87 cells both in vitro and in vivo. Consequently, TTIF emerges as a potential treatment option for patients with progressive or metastatic GBM.